The identity of Australia's northern-most giant pill-millipedes (Diplopoda, Sphaerotheriida) - Wesener, Thomas (Zootaxa, 2014)
The redescription of the lectotype of Zephronia larvalis Butler, 1878, from the Torres Strait islands between Australia and Papua-New Guinea, shows that it does not represent a member of the SE Asian Zephroniidae, but is a species of the Australian genus Cyliosoma of the Cyliosomatidae, C. larvalis new combination. The syntypes of Cyliosoma albertisii (Silvestri, 1895; Cyliosomatidae), Australia's northern-most Sphaerotheriida species described from Somerset (close to the Torres Strait islands), were restudied, and a lectotype was selected. C. albertisii is discovered to be a junior synonym of C. larvalis (Butler, 1878). C. larvalis, originally described as Zephronia larvalis, clearly belongs to the genus Cyliosoma, but displays some characters, such as a high number (25–30) of apical cones on the antennae, and the reduction of the spine-like projection of the stigmatic plates, that are unique in the genus and family. This synonymy confirms the Torres Strait giant pill-millipede fauna to be an Australian element, and not the first representative of a still undiscovered Papua-New Guinean fauna.